2000
DOI: 10.1080/09638190050086177
|View full text |Cite
|
Sign up to set email alerts
|

Export-led growth: a survey of the empirical literature and some non-causality results. Part 1

Abstract: The economic development and growth literature contains extensive discussions on relationships between exports and economic growth. One debate centres on whether countries should promote the export sector to obtain economic growth. An abundant empirical literature on this export-led growth (ELG) hypothesis has followed. We aim to contribute to this literature in two ways. In this paper, part 1, we provide a comprehensive survey of more than 150 export-growth applied papers. We describe the changes that have oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(105 citation statements)
references
References 34 publications
2
99
0
4
Order By: Relevance
“…First generation studies that did not consider the stationarity of the data and used simple correlation methods found strong support for the export-led hypothesis; however, more recent studies which have taken stationarity into account have found mixed support for the export-led and handmaiden hypotheses (see Giles and Williams, 2000;Ahmad, 2001 for reviews). There are a small number of papers that have examined Granger causality between exports and GDP for MENA countries (see e.g.…”
Section: Existing Literature and Hypothesesmentioning
confidence: 95%
“…First generation studies that did not consider the stationarity of the data and used simple correlation methods found strong support for the export-led hypothesis; however, more recent studies which have taken stationarity into account have found mixed support for the export-led and handmaiden hypotheses (see Giles and Williams, 2000;Ahmad, 2001 for reviews). There are a small number of papers that have examined Granger causality between exports and GDP for MENA countries (see e.g.…”
Section: Existing Literature and Hypothesesmentioning
confidence: 95%
“…Ahmad et al (1997) and Chen (2007) analyze the GLE and ELG hypotheses and find evidence for both. Bahmani-Oskooee and Economidou (2009), Bodman (1996), Chow (1987), Giles and Williams (2000), Greenaway and Sapsford (1994), Hsiao (1987), Oxley (1993), and Singh (2003) do not find evidence for both the GLE and ELG hypotheses; instead, some find support for the GLE and others for the ELG.…”
Section: Literature Reviewmentioning
confidence: 88%
“…From another point of view, the increase in a country's exports may indicate the reallocation of productive resources toward industries that are more efficient at a global level, which implies an increase in productivity; thus, there should be economic growth. Giles and Williams (2000) describe different approaches to develop models to test the ELG theory.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Opponents of the export-led growth hypothesis state that the markets of developed countries are not large enough to absorb the products of less developed countries (Giles & Williams, 2000a) and that, when compared with exports, other factors play a more crucial role in economic growth (Rodrik, 1992). Finally, while import demand in developed economies may be affected by factors such as the unpredictability of financial markets and the volatility of commodity prices, an export expansion may not result in a sustainable economic development in less developed countries.…”
Section: Theoretical Frameworkmentioning
confidence: 99%